Procurement challenges in public-sector agricultural development projects in Bangladesh - Md. Raquibuzzaman Khan; Nazia Tabassum; Niaz Ahmed Khan; Mohammad Jahangir Alam (Humanities & Social Sciences Communications, 2022)
Abstract The purpose of this paper is to identify and evaluate the key challenges to project procurement in public-sector agricultural development projects in Bangladesh. Being exploratory in nature, the study applied the modified Delphi method, the best worst method (BWM), and the interpretive structural modelling (ISM) approach sequentially for the investigation. Ten key procurement challenges were identified and validated through the use of a literature review and two rounds of modified Delphi with the input of 15 experts in the field. Then the BWM was applied to assess the responses of eight industry experts to estimate the relative importance of the challenges. After that, a second panel of ten experts was interviewed using ISM to look at the contextual relationships between the challenges. This led to a four-layer interpretive structural model and MICMAC (cross-impact matrix multiplication applied to classification) analysis of the challenges. Among the 10 key challenges, ‘lack of competent procurement staff’ is found to be the most significant challenge; whereas, based on the inter-relationships among the challenges, ‘political influence’ is identified as the most influential challenge. As a result, it is recommended that relevant professionals and policymakers address these challenges in terms of their relevance, relative dependencies, and influences in a holistic manner. This study addresses a knowledge gap by offering a thorough investigation of the challenges associated with public-sector agricultural project procurement in a developing country’s context. This makes it useful for professionals in the field, academics, policymakers, and future researchers.